Treating pediatric plaque psoriasis: challenges and solutions - Thomas, Jayakar (Pediatric Health Med Ther, 2016)
Psoriasis is a T-lymphocyte-mediated chronic inflammatory disorder involving the skin and joints. Nearly 3.5% of the population has been diagnosed to have psoriasis. In a dermatology department, almost one-third of psoriasis patients are in the pediatric age group. With an annual prevalence of up to 0.71%, childhood psoriasis can now be regarded as a frequently seen chronic inflammatory skin disorder having a significant impact on the quality of life. Based on the age of onset, psoriasis in children can be broadly classified as infantile psoriasis that can be mostly self-limited, psoriasis having an early onset, which needs specific treatment, and psoriasis that is associated with arthritis. Treating a child with psoriasis is a challenge, considering the physical development, body metabolism, rate of cutaneous absorption, and metabolism of drugs, which are quite different from those of the adults. The long duration of sun exposure for the rest of their life makes it more demanding while considering phototherapy in children. Long-term treatment of psoriasis, with phototherapy or drugs, needs critical evaluation in children. Hence, a thorough understanding of the disease in all its aspects will certainly help manage childhood psoriasis better. Timely diagnosis and adequate management not only arrest progression but also minimize the psychological burden caused by the disease, averting disfiguring states and evolution into a metabolic syndrome.